Delayed Diagnosis of Congenital Duodenal Stenosis in a 16-Year-Old Girl - Virtut Velmishi; Dritan Alushani; Ermira Dervishi; Saimir Heta; Spiro Sila; Paskal Cullufi (Case Reports in Medicine)
Background. Duodenal atresia or stenosis are different degrees of the same abnormality. They usually occur at the level of the ampulla of Vater and are thought to be an embryologic defect during the development of the foregut, leading to abnormal recanalization. Complete duodenal atresia is usually symptomatic in the early neonatal period, while partial obstruction (web, stenosis) may have a late presentation and a more challenging diagnosis such as in our case. Case Presentation. The patient, a 16-year-old girl, presented with abdominal pain, recurrent vomiting, and growth failure. An upper GI study with barium showed an image compatible with gastroptosis. Further diagnostic procedures confirmed a rare finding such as congenital duodenal stenosis. She underwent surgical intervention, and the recovery period was uneventful. Conclusion. Gastroptosis is not diagnostic for a particular disease. This rare radiological finding in children may obscure uncommon diagnosis, such as congenital duodenal stenosis, which can present a diagnostic challenge beyond early childhood.